Safe Prescription for Junior Doctors in Accordance with All Wales Prescribing Standards - Mavra Naz (The International Journal of Frontier Sciences, 2021)
Background: Prescribing errors are quite common and according to one estimate out of 100 patients admitted into UK hospitals 15 will have some form of prescribing error in their records. It is a general understanding that most of the time these errors are made due to lack of awareness. Severity of these errors can range from minor to major mistakes that can lead to fatal results.